Isoenergetic reduction of dietary macronutrients affects body composition, physical activity, and post-prandial hormone responses in lean and obese cats fed to maintain body weight - Godfrey, Hannah; Ribeiro, Érico de Mello; Verton-Shaw, Shoshana; Shoveller, Anna Kate; Kostiuk, Darcia; Kelly, Janelle; Saunders Blades, Jennifer; Verbrugghe, Adronie (Frontiers in Veterinary Science, 2025)
IntroductionHigh consumption of dietary carbohydrates (nitrogen-free extract, NFE) in extruded dry foods is postulated as a risk factor for feline obesity, though evidence is limited. This study utilized a three-test diet approach to isolate the effect of each macronutrient on body composition, voluntary physical activity, and serum satiety hormone response in lean and obese cats.Materials and methodsA pairwise isoenergetic reduction as % metabolizable energy (ME, using modified Atwater) of dietary macronutrients created a low-protein (LP; protein = 28%, fat = 40%, NFE = 32%ME), low-fat (LF; protein = 40%, fat = 30%, NFE = 30%ME), and low-carbohydrate (LC; protein = 36%, fat = 41%, NFE = 23%ME) diet. Cats (lean n = 9; obese n = 9) were fed the LP, LF, or LC diet to maintain body weight for 4-weeks in a 3 × 3 Latin square design. Voluntary physical activity was measured from day 15–21. On day 23, body composition was assessed by dual energy x-ray absorptiometry. On day 24, blood was collected for fasted and 6-h post-prandial serum satiety hormones. Data were analysed using SAS Studio via proc. GLIMMIX with significance set at p < 0.05.ResultsGreater lean soft tissue mass was observed for LF compared to LP and LC (p = 0.0101) though no other changes in body composition were observed. Daily food intake (g/d) differed among diets (LP: 56.14 ± 0.56; LF: 59.52 ± 0.59; LC: 56.50 ± 0.56; p = 0.0003) though energy intake (kcal/d) was similar (LP: 218.47 ± 2.32; LF: 220.42 ± 2.34; LC: 225.37 ± 2.39; p = 0.1076). Voluntary physical activity was similar for lean and obese cats (p = 0.4025). LP cats exhibited less physical activity during dark hours compared to LF and LC (p = 0.0155). No body condition effect was observed for serum leptin or ghrelin (p = 0.6243 and p = 0.6747). Obese cats on LP exhibited a lower serum leptin iAUC compared to obese cats on LC (PBC*Diet = 0.0093). Post-prandial serum ghrelin decreased in all cats whereas serum peptide YY (PYY) increased at 1-, 2-, and 3-h post-prandial (PTime = 0.0094 and PTime = 0.0050). Serum ghrelin was lower at 6-h post-prandial (PDiet*Time = 0.0030) and serum PYY was greater at 1-h post-prandial (PDiet*Time = 0.0086) for LC.DiscussionOverall, the LP, LF, and LC diets were not associated with differences in most parameters, supporting that cats are metabolically flexible if nutrient requirements are met. There may be benefits regarding satiety hormone responses to a LC diet in cats though more research is required.